O sistema multilateral do comércio e as novas necessidades da ordem econômica internacional: a democratização da OMC como mecanismo para promoção do desenvolvimento - Ana Luisa Soares Peres (2016)
Developing countries have played, in recent decades, a more assertive role in the international economic scene, marked by the consolidation of global governance and globalization. In the WTO, developing countries account for the vast majority of Members, but they still find it difficult to influence the decision-making system. This study proposes, accordingly, to examine the possibility of a more inclusive decision-making process, able to reflect the diversity of interests of the countries. The existence of a political element in this system does not undermine the hypothesis of adopting a democratic approach consistent with the WTO fundamentals of negotiation, such as the rule of consensus and the single undertaking. Priority should be given to procedures that allow rational argumentation, in a process of communicative action towards the adoption of a reasoned decision, which would be the most appropriate to the situation one seeks to regulate. WTO Members must have, in this sense, the same chances to participate in the negotiations, to achieve multilateral policies that provide proportional trading opportunities to all, especially regarding the socioeconomic development of Members. Development is included in the list of human rights and covers more than economic features. WTO multilaterally agreed policies have a direct impact on development and can be important tools for its promotion, which demonstrates that the matter is no longer limited to the national borders. The WTO has thus a duty to act jointly with its Members, to ensure that they have the conditions to fulfill their obligations to their constituents.